NURSE'S ACTIVITIES IN PRE-CHRISTMAS AT THE SUS NETWORK: A REVIEW OF THE LITERATURE (CIPEEX, 2022)
INTRODUCTION: GESTATIONAL EXPERIENCE IS A SPECIAL MOMENT IN A WOMAN'S LIFE, FOR THE BIRTH OF A CHILD IS A UNIQUE EXPERIENCE IN HER LIFE. THEREFORE IT DESERVES TO BE TREATED IN A HUMANIZED AND INTEGRAL WAY, BY TRAINED PROFESSIONALS AND BY THE MULTIPROFESSIONAL TEAM, WITH THE SUPPORT OF THE MANAGERS AND THE GOVERNMENT. THE PRENATAL PERIOD (PN) IS A TIME OF PHYSICAL AND PSYCHOLOGICAL PREPARATION FOR BOTH CHILDBIRTH AND MOTHERHOOD. THE ROLE OF THE NURSE IS EXTREMELY IMPORTANT IN THIS PERIOD, SINCE THEIR CONTRIBUTIONS REFLECT BETTER SUPPORT TO THE COMMUNITY AND IS CHARACTERIZED AS A MOMENT OF INTENSE LEARNING FOR BOTH PROFESSIONALS AND PATIENTS. OBJECTIVE: TO DESCRIBE THE ROLE OF NURSES IN PRENATAL CARE. METHODOLOGY: INTEGRATIVE LITERATURE REVIEW OF ARTICLES PUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL) AND AVAILABLE IN FULL TEXT IN THE DATABASES: LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS) AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND NURSING DATABASE (BDENF), IN THE PERIOD BETWEEN 2005-2015, IN THE PORTUGUESE LANGUAGE. FOR THE ANALYSIS OF THE DATA THE RECOMMENDATIONS OF MENDES ET AL. (2008), WHICH PROPOSES SIX STEPS FOR THE ELABORATION OF A GOOD, EFFECTIVE, PRECISE AND RELEVANT INTEGRATIVE REVIEW. RESULTS: 15 ARTICLES WERE INCLUDED IN THE REVIEW. TWO CATEGORIES EMERGED: HUMANIZATION IN PRENATAL CARE AND RECEIVING WITH QUALIFIED LISTENING; AND THE NURSE AS A MEMBER OF THE MULTIDISCIPLINARY TEAM AND A FUNDAMENTAL AGENT IN PN CARE. THE HUMANIZATION OF PN CARE IS EVIDENCED IN ORIENTATION, IN ACTIVE COMMUNICATION, UNDER THE INFLUENCE OF CONTENTS PREVIOUSLY ABSORBED BY THE PREGNANT WOMAN, WHETHER IN HER SOCIOCULTURAL CONTEXT OR EVEN IN THE FAMILY NETWORK. THE PREGNANT WOMEN SEEK TO SHARE THEIR DOUBTS WITH THE PROFESSIONAL WHO ATTENDED THEM, THE EXPERIENCES SEIZED AND / OR EXPERIENCED THAT THEY CONSIDER RELEVANT. BUILDING THUS, A TRUE RELATIONSHIP BETWEEN PROFESSIONALS AND CLIENT, IN ORDER TO PROVIDE THE BEST STATE OF HEALTH AND ILLNESS BASED ON QUALIFIED LISTENING AND CARE. THE NURSES WHO PERFORM THE NURSING CONSULTATIONS IN THE BASIC HEALTH UNITS (UBS), OFFER THE APPROPRIATE PROFESSIONAL ATTENTION TO THE PREGNANT WOMAN, SO THAT SHE FEELS WELCOMED. THE NURSE CAN USE A PLAN OF ACTION THAT STIMULATES THE PARTICIPATION OF THE PREGNANT WOMAN IN THE PN, BASED ON THE NEEDS IDENTIFIED AND PRIORITIZED IN THE CONSULTATION, ESTABLISHING THE INTERVENTIONS, ORIENTATIONS, AND REFERRALS TO REFERRAL SERVICES, PROMOTING THE INTERDISCIPLINARITY OF ACTIONS, WITH MEDICINE, DENTISTRY, NUTRITION, SOCIAL WORK AND PSYCHOLOGY. TOOLS FOR SUCH ARE EASILY EVIDENCED IN THE USE OF LIGHT AND HARD CARE TECHNOLOGY. CONCLUSION: WELCOMING AND BUILDING A BOND IS ESSENTIAL FOR THE MULTIPROFESSIONAL TEAM TO KNOW HOW TO DO IT. HUMANIZATION IN PN IS ESSENTIAL FOR THE PREGNANT WOMAN, SINCE IT IS AN ENVIRONMENT WHERE INTEGRAL AND QUALITY ASSISTANCE FOR THE HEALTH OF THE WOMAN AND HER CHILD CAN BE CREATED, CREATING A BOND OF TRUST, ACTIVE CONVERSATION AND QUALIFIED LISTENING WITHOUT ANY TYPE OF JUDGMENT.
Keywords: Prenatal. Nursing Care. Health Care